Analysis Of Factors Affecting Safety Satisfaction And Performance - Ayu Mutiara; Hunik Sri Runing Sawitri (LP2M IAIN Palopo, 2026)
This study aims to analyze the factors influencing safety/security satisfaction and safety performance in the SPAM WOSUSOKAS pipeline construction project. Specifically, it examines the effects of work equipment and environmental factors, human behavior, and organizational climate on safety/security satisfaction, as well as the effects of safety/security satisfaction and job satisfaction on safety performance. A quantitative approach with a causal research design was employed. Data were collected through a structured questionnaire using a census method involving 489 project workers. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that work equipment and environmental factors, human behavior, and organizational climate have positive and significant effects on safety/security satisfaction. Furthermore, safety/security satisfaction and job satisfaction significantly and positively affect safety performance. These findings suggest that improving safety performance requires an integrated approach that emphasizes safe work equipment and environments, compliance with safety procedures, and a safety-oriented organizational climate. This study provides empirical evidence and practical implications for enhancing occupational safety management in high-risk infrastructure construction projects.